The metabolic syndrome in children and adolescents - Hadjiyannakis, Stasia (Pulsus Group Inc, 2005)
The metabolic syndrome is a constellation of metabolic abnormalities that result in an increased risk for type 2 diabetes mellitus and cardiovascular disease in adults. It emerges when a person’s predisposition for insulin resistance is worsened by increasing central obesity and is largely confined to the overweight population. The United States National Cholesterol Education Program’s Adult Treatment Panel III report proposed a set of criteria for the clinical diagnosis of metabolic syndrome in the adult population. A uniform definition for the paediatric population is lacking. Despite this, several studies have demonstrated that features of the syndrome develop in childhood and that the syndrome is present in up to 30% of obese children (body mass index at or above the 95th percentile). Ninety per cent of obese children meet at least one of the five criteria. The degree of abnormality is related to the body mass index, waist circumference and fasting insulin levels. There appears to be a genetic predisposition to the development of the syndrome and certain ethnic groups are at increased risk. The intrauterine environment also appears to play a role. Insulin resistance should be targeted for treatment through exercise and dietary intervention. The role of pharmacotherapeutic agents remains unclear. A uniform definition of the metabolic syndrome for paediatric patients needs to be created. Early intervention should be instituted because many of the features of the syndrome track from childhood into adulthood.